2005
DOI: 10.1159/000087148
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Tumours of the Pancreas: Predictors of Survival after Surgical Treatment

Abstract: Aims: Neuroendocrine tumours of pancreatic and duodenal origin (NETP) are rare and we present a significant experience from a single centre. Methods: Data was collected on 44 patients who underwent surgery between 1988 and 2002. Since 1997, data have been recorded prospectively on a dedicated database. Results: Twenty-four patients had functioning tumours (16 insulinomas, 3 gastrinomas, 2 somatostatinomas, 1 vipoma, 1 glucagonoma and 1 carcinoid tumour). Nine functioning tumours and 13 non-functioning had a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 63 publications
2
42
1
5
Order By: Relevance
“…Surgical margin status is another significant indicator for long-term survival. Some studies have also concluded that aggressive resection of WD-Ca and PD-Ca can improve long-term survival [26,27,28]. Chung et al [30], Phan et al [31], and Madeira et al [32] reported surgical margin is a prognostic related factor, which also support the aggressive resection.…”
Section: Discussionmentioning
confidence: 96%
“…Surgical margin status is another significant indicator for long-term survival. Some studies have also concluded that aggressive resection of WD-Ca and PD-Ca can improve long-term survival [26,27,28]. Chung et al [30], Phan et al [31], and Madeira et al [32] reported surgical margin is a prognostic related factor, which also support the aggressive resection.…”
Section: Discussionmentioning
confidence: 96%
“…These tumors are symptomatic in 15% to 53% of the cases due to secretion of biologically active substances. The remaining are nonfunctioning and usually asymptomatic, although 50% are malignant and require surgical resection (6,13) . The literature reports 13 cases of accessory spleen simulating pancreatic tumors, all of them submitted to surgical resection (7,15,25) .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor grade and distant metastasis are the most important prognostic factors in determining survival in ANET. Other tumor properties, like nodal involvement, tumor size and resection margins, appear to be of lesser significance in predicting long-term survival [18]- [20].…”
Section: Survival and Long-term Follow Upmentioning
confidence: 99%